2016
DOI: 10.1039/c5nj02365c
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis, characterization and theoretical investigations of stannite phase CuZn2AlS4 nanocrystals

Abstract: The stannite-phase CuZn2AlS4 nanocrystals strongly absorb at visible wavelengths, which is suitable for solar energy material applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…4 is plotted for further understanding of the electronic properties. It also shows the direct band nature of CZMS, similar to the reported literature of CuZn 2 GaS 4 [9] and CuZn 2 AlS 4 compounds [10]. Around the Fermi energy (E F ), the d orbital of Cu hybridized with S-p in edge of valance band.…”
Section: Density Of States (Dos) and Band Structuresupporting
confidence: 87%
See 2 more Smart Citations
“…4 is plotted for further understanding of the electronic properties. It also shows the direct band nature of CZMS, similar to the reported literature of CuZn 2 GaS 4 [9] and CuZn 2 AlS 4 compounds [10]. Around the Fermi energy (E F ), the d orbital of Cu hybridized with S-p in edge of valance band.…”
Section: Density Of States (Dos) and Band Structuresupporting
confidence: 87%
“…It has been found that the compounds have band gap values of range ~1.20-1.72 eV in the visible region and have high absorption values, which indicate that these compounds offer decent optical properties to be used as inexpensive and nontoxic active layers in photovoltaic applications. The structural stability, structure, and composition, band structure of CuZn 2 AlS 4 has been reported earlier [10]. However, there is no systematic theoretical investigation to elucidate the structural, optoelectronic, and band structure properties of stannite and kesterite phase CuZn 2 InS 4 and CuZn 2 GaS 4 compounds.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…223,224 Experimental findings have demonstrated that these compounds have relatively large bandgaps, high SHG coefficients (2.76 eV and 1.8 × AGS for AgZnPS 4 and 3.38 eV and 0.8 × AGS for LiZnPS 4 ), and moderate birefringence values (0.05–0.08), indicating their potential as IR NLO materials deserving further investigation. However, in the case of the I-II 2 - III -S 4 type, structures like wurtzite AgCd 2 GaS 4 225,226 and stannite CuZn 2 AlS 4 , 227,228 which crystallize in the space groups Pmn 2 1 (No. 31) and I 4̄ 2 m (No.…”
Section: Diamond-like Templatesmentioning
confidence: 99%
“…The stannite phase CuZn 2 AlS 4 (CZAS) is an interesting material having a direct band gap (1.61 eV) with a suitable position of valence (5.4 eV) and conduction band (3.8 eV) and a relatively high absorption coefficient (≥10 5 cm –1 ) . Recently, Ghosh and co-workers , have synthesized CuZn 2 AS 4 and Cu 2 ZnAS 4– x (A = Al, Ga, In) semiconductors in which stannite phase is found to be more stable than zinc blende-, orthorhombic-, wurtzite-, and kesterite-type structures. Their results highlight the importance of low-cost absorber photovoltaic materials in solar energy applications due to their direct band gap (1.20–1.72 eV) and high optical absorption (>10 4 cm –1 ).…”
Section: Introductionmentioning
confidence: 99%